Pemahaman Hadis Kepemimpinan Quraisy: Studi Komparatif Tipologi Kepemimpinan Quraisy Dengan Tipologi Kepemimpinan Di Indonesia - Mila Melyani (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
Many people consider that the Quraish leadership hadith is no longer relevant today, because Islam has spread throughout the world. Then what about Indonesia because Indonesia is a Republican country. As a country with the most Muslim majority in the matter of appointing a leader, it is certainly a problem in itself. This study focuses on the meaning of the Quraish leadership tradition which can be universally understood and can also be contextualized for Indonesia by studying the typology of Quraish leadership and Indonesian leadership typology using comparative methodology. If applied from the hadith of the Quraish leadership into the context of Indonesia, the most important criterion that a leader must have in Indonesia is that of a generous, honest, trustworthy and fair nature.